An Analysis of Inbound Tourism in China - Yan, Peishuai (Université d'Ottawa | University of Ottawa, 2018)
The paper is an empirical study of China’s inbound tourism industry during the period 1980-2016. The condition of the industry is discussed, and an interpretation of statistics on the development of the industry is offered. The linear regression models, which link foreign exchange revenue, the number of foreign tourists and per tourist revenue with determinants such as the infrastructure of the tourism industry and the characteristics of tourists, are specified and estimated with panel data. The results show that real GDP per capita and relative PPPs do have a significant impact on foreign exchange revenue and the number of foreign tourists. However, the coefficient of the relative PPP is negative, which is inconsistent with expectations. Some of the tourism infrastructure variables also have a significant impact on the dependent variables.